Stardust [videorecording (DVD)] - Vaughn, Matthew, 1971-; O'Toole, Peter, 1932-2013; Pfeiffer, Michelle, 1957-; Danes, Claire, 1979-; Gaiman, Neil; Vess, Charles (Paramount Home Entertainment, 2007)
Tristan hopes to win the heart of his beautiful, but shallow love, Victoria. He promises to recover a star that fell somewhere beyond the stony Wall that sets between the mundane England and the fantasy kingdom of Stormhold. So Tristan sets forth on his own journey in Stormhold. Meanwhile in that magical land, the dying king has set his four surviving sons on a quest for the crown. And the witch Lamia is seeking the heart of the star for an entirely different purpose, one that involves her secret power.